The Impact of Transformational and Servant Leadership Models on Perceived Organizational Support, Job Satisfaction, and Life Satisfaction in the Ministry of Clergies of Synod of Gereja Kristus During The Covid-19 Pandemic in Indonesia - Oki Hermawati; Amirrudin Zalukhu; Wylen Djap; Erwin Santoso; Dylmoon Hidayat (Integritas: Jurnal Teologi, 2021)
The pandemic presents various struggles, including among church leaders and the clergy who serve specifically within the Synod of Gereja Kristus. The research conducted on the clergy looked at the two sides of leadership, i.e. transformational and servant leadership, where both leaders were associated with perceived organizational support, job satisfaction and life satisfaction factors for personal calling in serving as clergy. The results showed a positive and significant effect of transformational leadership on perceived organizational support and life satisfaction. Job satisfaction as a mediating variable also has a significant and positive effect on life satisfaction.